Effect of fat replacement by gluten and hydroxypropyl methylcellulose (HPMC) on the physicochemical, textural, and sensory properties of reduced-fat sausages - Kim, Yookyung; Song, Ka-Young (Progress in Nutrition, 2022)
This study aimed to investigate the effect of replacement with gluten and HPMC (hydroxypropyl methylcellulose) on physicochemical, textural, and sensory properties of meat-free product, soy sausages. Meat-free sausages showed more high moisture content (71.66%~74.05%) but meat sausage had the lowest moisture content (55.78%). For fatty acids composition, meat sausage showed large chain fatty acid (C18:1n-9 Cis, C18:1n-9 trans, C18:2n-6 trans, C20:0) while meat-free sausage showed small and medium chain (C8:0, C12:0, C13:0, C14:0, C14:1, C16:0, C16:1, C17:1). The disadvantage of texture and juiciness, which is the biggest problem of meat-free product can be compensated by use of 2% HPMC. 2% of HPMC addition had effects in consumer preference test so that the replacement of fat in meat product was confirmed with HPMC with benefits.